Teaching Strategies to Strengthen Cultural Identity in Bilingual Early Childhood Education (Docentes 2.0 Journal, 2026)
The communities of Peru's regions are sustained by their culture, as their inhabitants recognize their identity and mother tongue from an early age, developing a sense of belonging to a specific ethnic and social group. This research aimed to analyze the teaching strategies implemented in bilingual early childhood education institutions in Peru to strengthen cultural identity. The study was framed within the humanist paradigm, employing an interpretive method, a qualitative approach, a thematic narrative design, and a documentary-bibliographic and cross-sectional approach. Data collection was conducted through a systematic search and review of primary research in recognized academic databases, prioritizing publications within the past 5 years. Sources indexed in SciELO, REDIB, Latindex, Dialnet, OpenAIRE, ROAD, and Scopus were consulted, as well as university institutional repositories. To locate the studies, keywords and the logical operators AND, OR, and NOT were used. Subsequently, 22 scientific articles relevant to the research topic were selected and systematized. The findings revealed that various Peruvian communities develop their own teaching strategies aimed at strengthening cultural identity from early childhood education, integrating customs, the mother tongue, and community practices. It is concluded that most of Peru's indigenous peoples employ contextualized pedagogical approaches that significantly contribute to the preservation and consolidation of cultural identity in early childhood.
Keywords: Teaching strategies; cultural identity; early childhood education; bilingual